Economic load dispatch with pollution constraints / Maznida Shahila Mat Salleh - Mat Salleh, Maznida Shahila (1997)
his thesis attempts to explore the feasibility of developing relevant models, based on classical technique, to solve the EELD problem without line flow constraints to minimise the cost of generation or pollution level control simultaneously. The concept of total cost of generation and pollution level control is introduced for solving the EELD problem for varying degrees of compromise factor for the cost of generation and cost of pollution control required by the decision maker as reflected by his utility function.